Addressing Implementation Challenges of Minimum Service Standards in Local Government Using Soft System Methodology: A Case Study of Bekasi City, Indonesia - Desimaria, Maharina; Rahayu, Amy Yayuk Sri; Junarti, Junarti; Novia, Reni (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2024)
Minimum Service Standards (MSS) are specific provisions that must be fulfilled by local governments as a concurrent obligation targeted to reach 100% every year. However, as of 2023, Bekasi City has not achieved the set targets. The MSS Service Quality Achievement Index in Bekasi City is still relatively low, with all 6 MSS falling under the